Predicting microvascular invasion in hepatocellular carcinoma: A dual‐institution study on gadoxetate disodium‐enhanced MRI. (11th March 2022) - Jiang, Hanyu; Wei, Jingwei; Fu, Fangfang; Wei, Hong; Qin, Yun; Duan, Ting; Chen, Weixia; Xie, Kunlin; Lee, Jeong Min; Bashir, Mustafa R.; Wang, Meiyun; Song, Bin; et al.
Abstract: Background & Aims: Microvascular invasion (MVI) is an important risk factor in hepatocellular carcinoma (HCC), but its diagnosis mandates postoperative histopathologic analysis. We aimed to develop and externally validate a predictive scoring system for MVI. Methods: From July 2015 to November 2020, consecutive patients underwent surgery for HCC with preoperative gadoxetate disodium (EOB)‐enhanced MRI was retrospectively enrolled. All MR images were reviewed independently by two radiologists who were blinded to the outcomes. In the training centre, a radio‐clinical MVI score was developed via logistic regression analysis against pathology. In the testing centre, areas under the receiver operating curve (AUCs) of the MVI score and other previous MVI schemes were compared. Overall survival (OS) and recurrence‐free survival (RFS) were analysed by the Kaplan–Meier method with the log‐rank test. Results: A total of 417 patients were included, 195 (47%) with pathologically‐confirmed MVI. The MVI score included: non‐smooth tumour margin (odds ratio [OR] = 4.4), marked diffusion restriction (OR = 3.0), internal artery (OR = 3.0), hepatobiliary phase peritumoral hypointensity (OR = 2.5), tumour multifocality (OR = 1.6), and serum alpha‐fetoprotein >400 ng/mL (OR = 2.5). AUCs for the MVI score were 0.879 (training) and 0.800 (testing), significantly higher than those for other MVI schemes (testing AUCs: 0.648–0.684). Patients with model‐predicted MVI had significantly shorter OS (median 61.0 months vs not reached, P < .001) and RFS (median 13.0 months vs. 42.0 months, P < .001) than those without. Conclusions: A preoperative MVI score integrating five EOB‐MRI features and serum alpha‐fetoprotein level could accurately predict MVI and postoperative survival in HCC. Therefore, this score may aid in individualized treatment decision making.